2007
DOI: 10.1113/jphysiol.2006.123414
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hERG potassium currents in HEK‐293 cells by protein kinase C. Evidence for direct phosphorylation of pore forming subunits

Abstract: The human ether-a-go-go related gene (hERG) potassium channel is expressed in a variety of tissues including the heart, neurons and some cancer cells. hERG channels are modulated by several intracellular signalling pathways and these provide important mechanisms for regulating cellular excitability. In this study, we investigated muscarinic modulation of hERG currents and direct phosphorylation of channel subunits expressed in HEK-293 cells at physiologically relevant temperatures by protein kinase C (PKC). Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 41 publications
7
66
1
Order By: Relevance
“…hERG1 currents in NIH-3T3 cells were measured at room temperature using the whole-cell configuration of the patch-clamp technique as described previously (Cockerill et al, 2007). A561V and G628S hERG1 properties and the stability and efficacy of dofetilide and terfenadine in cell-culture conditions were investigated on hERG1 currents expressed in Xenopus oocytes by two-electrode voltage clamp (Perry et al, 2004).…”
mentioning
confidence: 99%
“…hERG1 currents in NIH-3T3 cells were measured at room temperature using the whole-cell configuration of the patch-clamp technique as described previously (Cockerill et al, 2007). A561V and G628S hERG1 properties and the stability and efficacy of dofetilide and terfenadine in cell-culture conditions were investigated on hERG1 currents expressed in Xenopus oocytes by two-electrode voltage clamp (Perry et al, 2004).…”
mentioning
confidence: 99%
“…A physiological interpretation of the observation falls beyond the scope of this study; it is worth noting, however, that general PKC sites have long been identified in several domains of Kv11.1, where some have been shown to be pathologically relevant. 14 Our results indicated a strongest effect for PKCε modulator peptides, followed closely by the PKCβI and PKCα, whereas PKCη and βII isoforms displayed effects of much lesser amplitudes. It was previously reported that PKCε also played a significant role in the regulation of many other voltage-gated ion channels (VGIC), as in the case of the L-type Ca 2+ channels, and the sodium channels Nav1.7 or Nav1.8.…”
Section: Discussionmentioning
confidence: 54%
“…A linear correlation could be drawn between V 1/2 and τ activation, as shown in Figure 4. The linear fit to the data indicates that a coupling between these parameters is preserved despite the differential effects caused by specific PKC isoform peptides 0.7 ± 0.1 (6) 420 ± 30 (6) 322 ± 34 (5) 1 ± 2 (6) -24 ± 2 (6) βIV5-3 0.7 ± 0.1 (14) 404 ± 28 (14) 339 ± 19 (15) 4 ± 1 (14) -23 ± 1 (14) αC2-4 0.6 ± 0.1 (14) 367 ± 26 (14) 422 ± 20 (12) 9 ± 1 (14) -22 ± 1 (14) ηV1-2 0.7 ± 0.1 (7) 293 ± 39 (7) 386 ± 25 (7) 11 ± 2 (6) -22 ± 1 (6) βIV5-3 0.6 ± 0.1 (7) 306 ± 23 (7) 454 ± 52 (5) 13 ± 2 (7) -22 ± 1 (7) δV1-1 0.6 ± 0.1 (6) 339 ± 50 (6) 598 ± 42 (4) 19 ± 1 (5) -24 ± 2 (4) εV1-7 0.7 ± 0.1 (7) 293 ± 39 (7) 539 ± 39 (6) 8 ± 1(7) -24 ± 1 (7) Values of Kv11.1 properties following treatments with the protein kinase C (PKC) modulators. The table is sorted to present the maximal effect on V 1/2 at the top.…”
Section: Effect Of Pkc Modulators On the Kinetics Of Kv111 Tail Currmentioning
confidence: 96%
See 1 more Smart Citation
“…This effect is dependent on consumption of PIP 2 at the membrane and direct binding of PIP 2 to HERG but occurs independently of calcium signaling or PKC activity (Bian et al, 2004;Bian & McDonald, 2007)). PKC regulation of HERG remains an active area of investigation where conclusive results await (Thomas, 2003) (Cockerill et al, 2007). For KCNQ1/KCNE1 and I Ks , Varnum et al showed that PKC stimulation decreased in I Ks due to KCNE1 phosphorylation at serine-102 (Varnum et al, 1993).…”
Section: Regulationmentioning
confidence: 99%